Testing of Chlorella/Scenedesmus microalgae consortia for remediation of wastewater, CO₂ mitigation and algae biomass feasibility for lipid production - Judita Koreivienė; Robertas Valčiukas; Jūratė Karosienė; Pranas Baltrėnas (Journal of Environmental Engineering and Landscape Management, 2014)
Industry, transport and unsustainable agriculture result in the increased quantity of wastewater, release of nutrients and emission of carbon dioxide that promotes eutrophication of water bodies and global climate change. the application of microalgae for phycoremediation, their biomass use for human needs may increase sustainability and have a positive effect on the regional development. The experiments were carried out in order to establish the feasibility of treating the local municipal wastewater with microalgae consortia and their biomass potential for biofuel production. The results revealed that Chlorella/Scenedesmus consortium eliminated up to 99.7–99.9% of inorganic phosphorus and up to 88.6–96.4% of inorganic nitrogen from the wastewater within three weeks. The ammonium removal was more efficient than that of nitrate. Chlorella algae grew better in diluted, while Scenedesmus – in the concentrated wastewater. The consortium treated wastewater more efficiently than a single species. The maximum biomass (3.04  g/L) of algal consortium was estimated in concentrated wastewater. Algae accumulated 0.65–1.37 g of CO2/L per day in their biomass. Tus, Chlorella/Scenedesmus consortium is a promising tool for nutrients elimination from the local wastewater under the climatic conditions specific to Lithuania. However, none of the two species were able to accumulate lipids under the nitrogen starvation conditions.